Outcome of Febrile Neutropenia in Children with Cancer: Experience from a Tertiary Health Care Center - Md Imrul Kaes; Afiqul Islam; Chowdhury Yakub Jamal; Mousumi Saha; Indira Chowdhury (KYAMC Journal, 2023)
Background: Febrile neutropenia (FN) is a serious event in children with cancer; associated with various complications and mentionable adverse outcome. Objective: To identify the outcome of febrile neutropenia in children with cancer. Materials and methods: This prospective observational study was conducted from October 2017 to November 2018 in the Department of Pediatric Hematology and Oncology, BSMMU. Children (age<18years) with malignancy who were admitted with febrile neutropenia or admitted patients who had developed febrile neutropenia onward were enrolled in this study. Finally, the outcome of each episode of FN was analyzed. Results: Total of 61 patients with 68 febrile neutropenic episodes were studied. Male patients were 62.29% and female patients were 37.70% with a mean age of 7 years. Majority were ALL (50.8%) followed by AML (29.5%), NHL (11.4 %) and solid tumor (8.1%). Bacterial infection was confirmed by culture in 14.7% episodes, 11.7% episodes had positive blood culture. Most of the isolated organisms were gram-negative (90%). Cough (39.7%), bleeding (19%) and diarrhea (17.64%) were the common clinical manifestations in those febrile neutropenic episodes. The mean duration of neutropenia was 9 days, 55.88% of episodes had prolonged neutropenia. Profound neutropenia was recorded in 47 % episodes and significantly associated with adverse outcome. Age ≥10 years also significantly associated with adverse outcome. The treatment success rate was achieved in76.4 % of episodes. A composite adverse event was observed in 23.52% of episodes; with mortality in 11.76%. Conclusion: Febrile neutropenia was a common complication in hematological malignancy. Although 76.4% episodes of febrile neutropenia had been treated successfully, mortality was significantly higher 11.76%. Profound neutropenia and age ≥10 were significant risk factors for dreadful outcome. KYAMC Journal Vol. 14, No. 01, April 2023: 07-10